Functional properties of fermented soymilk by Lactobacillus fermentum BM-325 - Myagmardorj, Batmunkh; Purev, Munkh-Erdene; Batdorj, Batjargal (Mongolian Journal of Chemistry, 2018)
Soy products have attracted much attention recently as carriers for probiotics. Fermentation of soymilk with lactic acid bacteria (LAB) was found to improve the nutritional and bioactivity values of consumed foods. The aim of this study was to evaluate functional properties of fermented soymilk with probiotic LAB strain Lactobacillus fermentum BM-325, based on their growth behavior, enzymes and antioxidant activities. Growth behavior such as viable cell number, pH, total acidity and enzyme activities were determined during fermentation period. Maximum number of viable cell was Log10 CFU·ml-1 12.6±0.9, maximum β-glucosidase activity was 78.9±3.9 U·mg-1 and maximum α-galactosidase activity was 97.7±4.8 U·mg-1, as well as antioxidant activity was IC50 0.04±0.002 mg·mL-1. Angiotensin converting enzyme inhibitory (ACEI) activity was determined in fermented soymilk and in partially purified peptide fraction. The ACEI activity was reached 60% after 20 h fermentation in soymilk. Our results suggested that fermentation of Lactobacillus fermentum BM-325 in soymilk for 4 h could be used to increase bioactivity of soymilk and suitable for the development of functional food.